Myxomycetes (Physarum) Physarum roseum - Kryvomaz, Т. І.; Minter, D. W.; Michaud, A. (CABI, 2017)
Diagnostic features. Sometimes similar to Physarum pulcherrimum Berk. & Ravenel, but more reddish, and with translucent stalks which are free from lime.
Keywords: myxomycetes; міксоміцети; Physarum roseum